Prolegomena to the Study of the "Miracles of St Menas" - Piwowarczyk, Przemysław (Vox Patrum, 2025)
This article aims to outline the key developments in the early history of the Miracles of St Menas. It presents arguments supporting the primacy of the Greek text over the Coptic version. The article then examines the time and place of the original composition, locating it at Abū Mīnā in the latter half of the 6th century. The complex process of the collection's development spanned several centuries, with key stages including the formation of the 13-miracle collection after 614, its translation into Coptic before 641, the subsequent expansion of the Coptic collection, and the revision of the Greek original. Finally, the article argues that the original collection had a local character, aimed primarily at the local community.